Susceptibility of maize hybrids to corn smut diseas - Frommer, Dóra; Radócz, László; Veres, Szilvia; Lévai, László (Acta Agraria Debreceniensis, 2016)
Corn smut disease is one of the most common maize diseases. In the previous years the disease lost from its importance, however nowadays it is becoming more and more important and widespread. The protection against it encounters great difficulties, therefore it is important to emphasize prevention and resistance based protection. The aim of the research was to investigate under laboratory circumstances the resistance of Hungary’s most commonly cultivated maize hybrids to corn smut disease. Twelve species were investigated. We distinguished two susceptibility groups within the hybrids based on the investigated parameters. The results are intended to assist the protection against corn smut disease and to make a suggestion for the farmers so that they could apply more environmental friendly and economical production.